Pengaruh Fasilitas Kerja, Kesejahteraan, dan Stres Kerja Terhadap Kinerja Guru pada Tingkat Sekolah Menengah Pertama - Nurindah Suminaringwulan; Suhana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Teacher performance is a crucial factor in determining the quality of education, especially at the junior secondary school level, which plays a strategic role in shaping students’ character and academic foundation. This study examined the influence of workplace facilities, job well-being, and work-related stress on teacher performance in junior high schools within Rayon 05, Semarang. A quantitative approach was employed using a survey method through the distribution of questionnaires. The population included all junior high school teachers in Rayon 05, and the sample consisted of 148 teachers from 11 schools, determined using the Slovin formula. Proportionate stratified random sampling was applied to ensure balanced representation across schools. Data were analyzed using multiple linear regression with the assistance of SPSS software. The results indicated that workplace facilities and job well-being had a positive and significant simultaneous effect on teacher performance, while work-related stress did not have a significant effect. These findings suggest that adequate facilities and a supportive work environment contribute to improving teacher performance. Educational institutions are therefore encouraged to strengthen both infrastructure and teacher well-being as part of broader efforts to enhance educational quality.